Iridescent Glass Surfaces for Jewelry and Wearable Art - Santos, Isabela Aiache (2019)
This research explores creativity through process, within an interdisciplinary practice between art and science. This merging of disciplines stimulated the author to follow a particular path to discovery using physical tools given by the Vicarte research unit, and a mental contemplative space made possible through fluid creation without commercial purpose. In this dynamic scenario, glass as a technically challenging material also favored the development of skills in problem solving, leading to news discoveries. As a consequence, a new and environmentally friendlier method for creating iridescent surfaces on glass silver mirrors is presented utilizing an electrochemical anodizing process. This process diverges from the traditional methods used to obtain iridescent glasses that where potentially toxic. The rise of said methodology inspired intense practical research that later lead to the creation of conceptually inspired wearable glass pieces. Additionally, the work encompasses beliefs spread by the Contemporary Jewelry Movement, which define a category of objects that are involved with fine art practice and critical thinking. The resulting glass objects, conforming to different areas of the body, were used to challenge to the notion of jewelry practice and also questioned the methods with which we learn and think creatively.